Project Ready: Encounters and Challenges of English Pre-Service Teachers - Valenzuela, Christian Loid; Sardina, Dante (Asian Journal of Community Services, 2024)
The study aimed to explore the encounters and challenges of the 15 pre-service English teachers who participated in Project Ready a community-based reading program. Through document and thematic analyses of the narrative report and reflection paper of the participants, the researchers interpret and illicit meaning as their bases for exploring the effects of Project Ready. The study concluded that Project Ready is deemed to be a significant community-based reading program as it offers both the pre-service English teachers and students a first-hand opportunity in teaching reading comprehension. The researchers recommend that schools and its stakeholders must prioritize creating engaging reading classroom environment, promoting multisensory and collaborative reading approaches and developing customized reading intervention.